A temperature-adaptive component-dynamic-coordinated strategy for high-performance elastic conductive fibers - Yue Zhang; Zechang Ming; Zijie Zhou; Xiaojie Wei; Jingjing Huang; Yufan Zhang; Weikang Li; Liming Zhu; Shuang Wang; Mengjie Wu; Zeren Lu; Xinran Zhou; et al. (Nature Communications)
Abstract Temperature-adaptive elastic conductive fibers (ECFs) are crucial for seamlessly integrating electronic textiles, promoting the development of wearables, soft robotics, and high/low-temperature electronics. Realizing ECFs with balanced elasticity, conductivity, and temperature adaptivity remains challenging due to the difficulty of coupling the mechano-electrical-thermal properties at a microscale fiber. We design a wet-spun ECF consisting of thermoplastic polyurethane (TPU), silver flakes (AgFKs) and liquid metal microspheres (LMMSs) with regularly arranged filler architecture, revealing a cold/thermal stretching activated tricomponent-dynamic-coordination mechanism for autonomously-enhanced electrical conductivity (from ~1070 S cm−1 at 25 °C to 1160 S cm−1 at −30 °C and 3020 S cm−1 at 180 °C) and improved electrical stability to sustain 1000 stretching cycles (60% strain at 80 °C). The fiber exhibits scalability and favorable knittability, demonstrating e-textiles such as biomedical electrodes, high/low-temperature near-field communication gloves, and intelligent firefighting suits. The autonomous mechano-thermo-electrical coupling strategy can inspire high-performance and environment-adaptive ECFs for extreme applications.